Hubungan Pengetahuan Dengan Kejadian Hipertensi Pada Kehamilan Di Wilayah Kerja Puskesmas Telaga Dewa Kota Bengkulu - Muhamad Firmansyah; Murwati Murwati; Kartika Murya Ningrum (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Hypertension, or high blood pressure, is a condition characterized by persistently elevated blood pressure in the blood vessels. Hypertension is defined as systolic blood pressure ≥ 140 millimeters of mercury (mmHg) and diastolic blood pressure ≥ 90 mmHg (Annisa et al. 2024). The purpose of this study was to determine the relationship between knowledge and the incidence of hypertension during pregnancy in the Telaga Dewa Community Health Center (Puskesmas) area of ​​Bengkulu City in 2026. The study used a cross-sectional design with accidental sampling. Data were collected through questionnaires from 73 pregnant women visiting the Telaga Dewa Community Health Center. Data analysis was performed using univariate and bivariate methods. The results showed that almost all respondents (42 respondents) had good knowledge, and most (44 respondents) did not experience hypertension. The bivariate analysis revealed a significant association between knowledge and the incidence of hypertension during pregnancy, with a p-value of 0.029 and a p-value of <0.05. It is recommended that the Telaga Dewa Community Health Center in Bengkulu City provide services and provide counseling regarding the prevention of hypertension during pregnancy to reduce the risk of complications.